P1-S2.13 The impact of the 2010 Winter Olympic Games on sex work patterns, safety and sex worker vulnerability to HIV and sexually transmitted infections. (10th July 2011) - Deering, K; Chettiar, J; Chan, K; Taylor, M; Montaner, J; Shannon, K
Abstract : Background: Large-scale international sports events such as the 2010 Winter Olympics Games in Vancouver, Canada can have significant impacts on the vulnerability of sex workers (SWs) to HIV and sexually transmitted infections (STIs). SWs in Vancouver continue to face extreme vulnerabilities to violence and HIV/STIs. Despite significant focus on the social legacy of large-scale sports events, there is surprisingly limited research evaluating the impact of such events on sex work. This study therefore examined the impact of the 2010 Olympic time period on sex work patterns, safety and HIV/STI vulnerability of SWs in Vancouver. Methods: Data were used from a screening questionnaire for a longitudinal cohort study of 230 SWs from January to July 2010. Bivariate and multivariable logistic regression was used to examine the impact of time period (pre/during-Olympics vs post-Olympics) on sex work patterns, safety and HIV/STI vulnerability in the last 30 days. Results: Overall, the median age of respondents was 33 years (IQR—28–40), and 106 (51.2%) SWs were non-Caucasian. In multivariable analysis (after adjusting for social and environmental factors) in the pre/during-Olympics period compared to post-Olympics, we found significantly higher odds of respondents reporting more police stopping SWs without arrest (adjusted ORs[AOR]—3.95, 95% CIs 1.92 to 8.14), reporting a decrease in the numbers of clients available (AOR—1.97, 95% CI 1.11 to 3.48), reporting difficulty hooking up with clients due to road closures/construction (AOR 7.68, 95% CI 2.46 to 23.98) and a decrease in the numbers of clients available (AOR 3.59, 95% CI 1.79 to 7.19). We found no significantly increased odds in new/trafficked SWs in the Olympic time period. Conclusions: There were significant changes in sex work patterns, safety and HIV/STI vulnerability of SWs immediately before and during the 2010 Winter Olympics compared to post-Olympics. Fears over an influx of new SWs or human trafficking appear to be unfounded. Displacement of SWs away from main streets/commercial areas has significant public health implications, since this previously has been shown to promote violence and coercive unprotected sex, and increase risk for HIV/STIs. Safer sex work spaces such as indoor brothels and policy reforms should be considered both in Canada and by other host countries of large-scale events to reduce the vulnerability of SWs to HIV from displacement and disruption.